Positive electrode material and preparation method thereof, lithium ion battery and electric device
By adjusting the micromorphology and grain size of lithium manganese iron phosphate, combined with the preparation methods of sintering, grinding and spray drying, the problems of low compaction density and electrochemical performance of the positive electrode material are solved, and the effects of high energy density and cycling stability are achieved.
Patent Information
- Application Number
- CN202411961136.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-07
AI Technical Summary
The compaction density and electrochemical performance of the existing lithium manganese iron phosphate cathode materials are low, and the preparation method has cost and safety problems.
By adjusting the unit cell volume and grain size of lithium manganese iron phosphate, a preparation method including sintering, grinding and spray drying is used to prepare a positive electrode material with high compaction density and excellent electrochemical properties.
The high energy density and excellent cycle stability of the cathode material are achieved, the process is simplified, the cost is reduced, and it is suitable for large-scale industrial production.
Smart Images

Figure CN119581553A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and specifically relates to a positive electrode material and a preparation method thereof, a lithium-ion battery and an electrical device. Background Art
[0002] In recent years, under the market demand trend of improving the comprehensive performance of lithium-ion batteries, phosphate batteries are undergoing an upgrade from lithium iron phosphate (LFP) to lithium manganese iron phosphate (LMFP). On the basis of LFP, a certain amount of manganese is doped and the ratio of its atomic number to iron is adjusted to increase the voltage platform of the material, thus generating LMFP products. LMFP has a higher voltage platform than LFP, and its theoretical energy density is expected to be 15-20% higher than LFP, which can break through the energy density bottleneck faced by LFP to a certain extent. It not only has a higher voltage platform, higher energy density, and better low-temperature performance, but also retains the high safety and low-cost advantages of LFP. However, its compaction density, electronic conductivity and lithium ion conductivity are low. Therefore, how to improve the compaction density and electrochemical performance of LMFP has received continuous attention from technicians in this field.
[0003] In order to improve the electrochemical performance of LMFP cathode materials, researchers usually use nano-sizing, carbon coating, ion doping and other modification methods to improve LMFP cathode materials. For example, by adding manganese source, iron source and surfactant into acidic hydrogen peroxide solution, and then transferring it to a high-temperature and high-pressure reactor for reaction, and then filtering and sintering to obtain LMFP material, however, in the above preparation method, acidic hydrogen peroxide is an explosive and dangerous substance, and a high-temperature and high-pressure reactor is required, which has prominent cost and safety issues. Therefore, the preparation method of lithium manganese iron phosphate cathode material still needs to be further improved. Summary of the invention
[0004] This application is based on the inventor's discovery and understanding of the following facts and problems:
[0005] The inventors have found that the unit cell volume and grain size of LMFP materials are closely related to the capacity and compaction density of the materials. Through certain process adjustments, the prepared LMFP materials have specific microscopic morphology, unit cell volume, and grain size, and the prepared lithium-ion batteries have higher compaction density and excellent electrochemical performance.
[0006] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present application proposes a positive electrode material with high energy density or excellent cycle stability, a preparation method thereof and a lithium ion battery.
[0007] In a first aspect, the present application provides a positive electrode material, including lithium manganese iron phosphate, wherein the unit cell volume of the lithium manganese iron phosphate is Therefore, the positive electrode material has higher compaction density, electronic conductivity and ionic conductivity.
[0008] In some embodiments, the unit cell volume of the lithium manganese iron phosphate is In some other embodiments, the unit cell volume is This is beneficial to the deintercalation of lithium ions, thereby improving the cycle life of lithium-ion batteries.
[0009] In some embodiments, the lithium manganese iron phosphate has a composition shown in Formula I:
[0010] Li a Mn x Fe y M 1-x-y (PO4) b Formula I
[0011] Among them, 0.90≤a≤1.20, 0.30≤x≤0.95, 0.05≤y≤0.70, 0.95≤b≤1.10;
[0012] M is at least one selected from Ti, Mg, Zn, Cu, Sr, Al, Zr, Y, Co, W, Ca, Nb, Sn, Sb, Mo, V, B, and Si;
[0013] 1.03≤b / (x+y)≤1.15.
[0014] With the above composition, the lithium iron manganese phosphate positive electrode material not only has a higher voltage platform, higher energy density, and better low-temperature performance, but also has higher compaction density, electronic conductivity, and ionic conductivity.
[0015] In some embodiments, 0.95≤a≤1.15; in other embodiments, 1.00≤a≤1.10; in some specific examples, 1.02≤a≤1.08.
[0016] In some embodiments, 1.00≤b≤1.09; in other embodiments, 1.01≤b≤1.07.
[0017] In some embodiments, 0.90≤x+y≤1.00; in other embodiments, 0.95≤x+y<1.00.
[0018] In some embodiments, 1.05≤b / (x+y)≤1.10.
[0019] In some embodiments, the lithium manganese iron phosphate satisfies: 80nm≤L 10 ≤200nm; in some other embodiments, 100nm≤L 10 ≤180nm.
[0020] In some embodiments, the lithium manganese iron phosphate satisfies: 150nm≤L 50 ≤300nm; in some other embodiments, 160nm≤L 50 ≤260nm.
[0021] In some embodiments, the lithium manganese iron phosphate satisfies: 200nm≤L 90 ≤500nm; in some other embodiments, 220nm≤L 90 ≤480nm.
[0022] Among them, L 10 , L 50 , L 90 It is the grain size corresponding to the cumulative volume percentage of the grain size Ln of the lithium manganese iron phosphate reaching 10%, 50% and 90% respectively. The grain size within the above range is conducive to shortening the migration path of lithium ions in the positive electrode material and increasing the lithium ion diffusion rate, that is, the material has better kinetic properties, and the appropriate grain size can increase the compaction density of the positive electrode material.
[0023] In some embodiments, the compaction density of the lithium manganese iron phosphate is 2.3 g / cm 3 ~2.6g / cm 3 This is beneficial to improving the energy density of lithium-ion batteries.
[0024] The second aspect of the present application provides a method for preparing a positive electrode material, comprising:
[0025] Sintering a first mixed material containing a lithium source, an M source, a phosphorus source, a manganese source, and an iron source to obtain a primary sintered material, wherein the primary sintered material includes secondary particles, wherein the secondary particles are formed by agglomerating a plurality of primary particles, and a primary particle size P of the primary particles satisfies 100 nm ≤ P ≤ 500 nm;
[0026] Mixing the primary sintered material with a carbon source in a solvent and performing a second grinding to obtain a second mixed material;
[0027] The second mixed material is subjected to a second spray drying to obtain a second spray-dried material;
[0028] The second spray-dried material is subjected to secondary sintering to obtain the lithium manganese iron phosphate.
[0029] The present application obtains a more suitable primary particle size by regulating the conditions of the primary sintering treatment, thereby improving the compaction density of the positive electrode material. The preparation method is simple in process and suitable for large-scale industrial production.
[0030] In some embodiments, the first mixed material is subjected to a first spray drying to obtain a first spray dried material; the first spray dried material is heated to 400°C to 700°C at a heating rate of 1°C / min to 5°C / min under an inert atmosphere, kept at this temperature for 3h to 15h, and sintered once to obtain a primary sintered material. This can promote the reaction and facilitate the growth of primary particle crystals.
[0031] In some embodiments, the molar ratio of phosphorus in the phosphorus source to manganese in the manganese source and iron in the iron source, n(P) / n(Mn+Fe), is 1.03:1 to 1.15:1. This can make the phosphating reaction more complete and increase the compaction density of the positive electrode material.
[0032] In some embodiments, the D of the first mixed material 50 The thickness is 0.1 μm to 0.5 μm, which is beneficial to improving the rate performance of lithium-ion batteries.
[0033] In some embodiments, the D of the second mixture 50 The thickness is 0.2 μm to 0.6 μm, which is beneficial to improving the rate performance of lithium-ion batteries.
[0034] In some embodiments, the mass ratio of the carbon source to the primary sintering material is 2:100 to 20:100, which is beneficial to promote the reaction and improve the sintering efficiency.
[0035] In some embodiments, the manganese source includes at least one of manganese sulfate, manganese carbonate, manganese nitrate, and manganese tetraoxide. Thus, the source of the material is wide and the cost is low.
[0036] In some embodiments, the iron source includes at least one of ferric phosphate, ferric nitrate, ferric sulfate, ferrous oxalate, ferrous carbonate, and ferric oxide. Thus, the material source is wide and the cost is low.
[0037] In some embodiments, the phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate, lithium dihydrogen phosphate, and lithium phosphate. Thus, the material source is wide and the cost is low.
[0038] In some embodiments, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium phosphate, and lithium nitrate. Thus, the material source is wide and the cost is low.
[0039] In some embodiments, the M source includes at least one of an oxide, a hydroxide, and a carbonate containing the element M. Thus, the source of the material is wide and the cost is low.
[0040] In some embodiments, the carbon source includes at least one of glucose, sucrose, and an organic polymer. Thus, the material source is wide and the cost is low.
[0041] In some embodiments, the second spray-dried material is subjected to secondary sintering, comprising: heating to 600°C to 800°C at a heating rate of 1°C / min to 3°C / min under an inert atmosphere, and keeping the temperature for 5h to 20h, thereby promoting the reaction and improving the reaction efficiency.
[0042] The third aspect of the present application provides a lithium-ion battery, comprising the positive electrode material described in the first aspect of the present application or the positive electrode material prepared by the method described in the second aspect of the present application. Thus, the lithium-ion battery has a higher energy density and excellent cycle stability.
[0043] The fourth aspect of the present application provides an electric device, comprising the lithium-ion battery described in the third aspect of the present application. Thus, the electric device has a longer service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a SEM photograph of the primary sintered material of Example 1 of the present application.
[0045] Figure 2 This is a SEM photograph of the positive electrode material of Example 1 of the present application.
[0046] Figure 3 It is a grain size distribution diagram of the positive electrode materials of Examples 1 to 2 and Comparative Examples 1 to 2 of the present application.
[0047] Figure 4 This is a SEM photograph of the primary sintered material of Comparative Example 1 of the present application.
[0048] Figure 5 This is a SEM photograph of the positive electrode material of Comparative Example 2 of the present application. DETAILED DESCRIPTION
[0049] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.
[0050] In a first aspect, the present application provides a positive electrode material, including lithium manganese iron phosphate, wherein the unit cell volume of the lithium manganese iron phosphate is Therefore, the positive electrode material has higher compaction density, electronic conductivity and ionic conductivity.
[0051] In some embodiments, the unit cell volume of the lithium manganese iron phosphate is For example, it can be or etc.; In some other embodiments, the unit cell volume is This is beneficial to further improve the compaction density, electronic conductivity and ionic conductivity of the positive electrode material.
[0052] In some embodiments, the lithium manganese iron phosphate has a composition shown in Formula I:
[0053] Li a Mn x Fe y M 1-x-y (PO4) b Formula I
[0054] Among them, 0.90≤a≤1.20, 0.30≤x≤0.95, 0.05≤y≤0.70, 0.95≤b≤1.10;
[0055] M is at least one selected from Ti, Mg, Zn, Cu, Sr, Al, Zr, Y, Co, W, Ca, Nb, Sn, Sb, Mo, V, B, and Si;
[0056] 1.03≤b / (x+y)≤1.15.
[0057] With the above composition, the lithium iron manganese phosphate positive electrode material not only has a higher voltage platform, higher energy density, and better low-temperature performance, but also has higher compaction density, electronic conductivity, and ionic conductivity.
[0058] In some embodiments, 0.95≤a≤1.15, for example, it can be 0.95, 0.98, 1, 1.05, 1.08, 1.1 or 1.15, etc.; in other embodiments, 1.00≤a≤1.10; in some specific examples, 1.02≤a≤1.08.
[0059] In some embodiments, 1.00≤b≤1.09, for example, it can be 1, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08 or 1.09, etc.; in other embodiments, 1.01≤b≤1.07.
[0060] In some embodiments, 0.90≤x+y≤1.00, for example, it can be 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99 or 1.00, etc.; in other embodiments, 0.95≤x+y<1.00.
[0061] In some embodiments, 1.05≤b / (x+y)≤1.10, for example, it can be 1.05, 1.06, 1.07, 1.08, 1.09 or 1.10, etc.
[0062] In some embodiments, the lithium manganese iron phosphate satisfies: 80nm≤L 10≤200nm, for example, it can be 80nm, 100nm, 120nm, 140nm, 160nm, 180nm or 200nm, etc.; in some other embodiments, 100nm≤L 10 ≤180nm.
[0063] In some embodiments, the lithium manganese iron phosphate satisfies: 150nm≤L 50 ≤300nm, for example, it can be 150nm, 170nm, 190nm, 210nm, 230nm, 250nm, 270nm or 300nm, etc.; in some other embodiments, 160nm≤L 50 ≤260nm.
[0064] In some embodiments, the lithium manganese iron phosphate satisfies: 200nm≤L 90 ≤500nm, for example, it can be 200nm, 250nm, 300nm, 350nm, 400nm, 450nm or 500nm; in some other embodiments, 220nm≤L 90 ≤480nm.
[0065] Among them, L 10 , L 50 , L 90 is the grain size corresponding to the volume cumulative percentage of the grain size Ln of the lithium manganese iron phosphate reaching 10%, 50% and 90% respectively. It should be noted that the grain size Ln is obtained by using the powder X-ray diffraction pattern obtained by using CuKα ray powder X-ray diffraction measurement and the Fundamental Parameter method fitting algorithm to perform size statistics. 50 As a physical quantity representing the median of volume distribution, it can represent the size of the grain size. The smaller the grain size, the shorter the migration path of lithium ions in the positive electrode material and the higher the diffusion rate, that is, the material has better kinetic properties, but too small a grain size may also lead to a lower compaction density of the material. 10 , L 50 , L 90 When the above range is met, the compaction density and electrochemical specific capacity are better than those in other ranges.
[0066] In some embodiments, the compaction density of the lithium manganese iron phosphate is 2.3 g / cm 3 ~2.6g / cm 3 , for example, it can be 2.3 g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 or 2.6g / cm 3 Etc. This is beneficial to improving the energy density of lithium-ion batteries.
[0067] The second aspect of the present application provides a method for preparing a positive electrode material, comprising:
[0068] S1: Sintering a first mixed material containing a lithium source, an M source, a phosphorus source, a manganese source, and an iron source to obtain a primary sintered material, wherein the primary sintered material includes secondary particles, wherein the secondary particles are formed by agglomeration of multiple primary particles, and a primary particle size P of the primary particles satisfies 100nm≤P≤500nm.
[0069] Specifically, the size P of the primary particles may be 100 nm, 120 nm, 150 nm, 180 nm, 200 nm, 220 nm, 250 nm, 280 nm, 300 nm, 320 nm, 350 nm, 380 nm, 400 nm, 420 nm, 450 nm, 480 nm or 500 nm. When the primary sintering material has a larger primary particle size, it is beneficial to form a grain size L that meets the requirements during the second grinding and sintering. n Distribution requirements for lithium iron manganese phosphate secondary particle materials.
[0070] In this step, the specific method of mixing the lithium source, M source, phosphorus source, manganese source, and iron source is not particularly limited. For example, a mixer (such as a ball mill) can be used for mixing. After mixing, the first mixed material can be dispersed in a solvent according to a certain solid content, and then a first grinding is performed. When the particle size D of the material is 50 When the particle size is 0.1 μm to 0.5 μm, the first spray drying process is performed.
[0071] In some embodiments, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium phosphate, and lithium nitrate. Thus, the material source is wide and the cost is low.
[0072] In some embodiments, the M source includes at least one of an oxide, a hydroxide, and a carbonate containing the element M. Thus, the source of the material is wide and the cost is low.
[0073] In some embodiments, the phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate, lithium dihydrogen phosphate, and lithium phosphate. Thus, the material source is wide and the cost is low.
[0074] In some embodiments, the manganese source includes at least one of manganese sulfate, manganese carbonate, manganese nitrate, and manganese tetraoxide. Thus, the source of the material is wide and the cost is low.
[0075] In some embodiments, the iron source includes at least one of ferric phosphate, ferric nitrate, ferric sulfate, ferrous oxalate, ferrous carbonate, and ferric oxide. Thus, the material source is wide and the cost is low.
[0076] It should be noted that the phosphorus source, manganese source, and iron source are selected from common commercial raw materials, and this application is not specifically limited. They can be independent raw materials of phosphorus, manganese, and iron, or combined raw materials of phosphorus + manganese, phosphorus + iron, manganese + iron, and phosphorus + manganese + iron. Those skilled in the art can choose as needed. As an example, the combined raw materials of phosphorus + manganese, phosphorus + iron, manganese + iron, and phosphorus + manganese + iron can be selected from manganese phosphate, iron phosphate, ferromanganese oxide, ferromanganese hydroxide, ferromanganese carbonate, ferromanganese phosphate, ferromanganese pyrophosphate, etc.
[0077] In some embodiments, the molar ratio of phosphorus in the phosphorus source to manganese in the manganese source and iron in the iron source, n(P) / n(Mn+Fe), is 1.03:1 to 1.15:1, for example, 1.03:1, 1.05:1, 1.08:1, 1.1:1, 1.13:1 or 1.15:1, etc. This can make the phosphating reaction more sufficient and increase the compaction density of the positive electrode material.
[0078] In this article, the appropriate P / (Mn+Fe) molar ratio can make the phosphating reaction more sufficient, and the appropriate primary sintering temperature and holding time can also promote the reaction, which is conducive to the growth of primary particle crystals. When the P / (Mn+Fe) molar ratio is too large, the primary sintering temperature is too high, and the holding time is too long, the primary particle size will be too large, which will not only affect the efficiency of the secondary grinding, increase the grinding energy consumption, but also affect the capacity of the finished product of the lithium iron manganese phosphate positive electrode material; and when the P / (Mn+Fe) molar ratio is too low, the primary sintering temperature is too low, and the holding time is too short, the primary particle size of the obtained primary sintered material will be reduced, and after secondary grinding and sintering, the grain size is small, thereby affecting the compaction density of the finished product of the lithium iron manganese phosphate positive electrode material. The P / (Mn+Fe) molar ratio, the primary sintering temperature and the holding time meet the range described in this application, and show better compaction density and capacity than other ranges.
[0079] In some embodiments, the first mixed material is subjected to a first spray drying to obtain a first spray dried material; the first spray dried material is heated to 400°C to 700°C (such as 400°C, 500°C, 600°C or 700°C) at a heating rate of 1°C / min to 5°C / min (such as 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min) under an inert atmosphere, and kept warm for 3h to 15h (such as 3h, 5h, 8h, 10h, 12h or 15h), and sintered once to obtain a primary sintered material. This can promote the reaction and facilitate the growth of primary particle crystals.
[0080] In some embodiments, the D of the first mixed material 50The thickness is 0.1 μm to 0.5 μm, for example, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm or 0.5 μm, etc. This is beneficial to improving the rate performance of the lithium ion battery.
[0081] In the particle size distribution, D 50 Also known as the median particle size, it means that 50% of the volume of particles is less than or equal to this value. It can be measured by a Malvern particle size tester: disperse the positive electrode material in a dispersant (ethanol, acetone or other surfactant), ultrasonicate for 30 minutes, add the sample to the Malvern particle size tester, and start the test.
[0082] S2: mixing the primary sintered material and the carbon source in a solvent and performing a second grinding to obtain a second mixed material.
[0083] In some embodiments, the carbon source includes at least one of glucose, sucrose, and an organic polymer, wherein the carbon source accounts for 1% to 20% of the theoretical yield of lithium manganese iron phosphate.
[0084] In some embodiments, the mass ratio of the carbon source to the primary sintering material is 2:100 to 20:100, for example, 2:100, 5:100, 8:100, 10:100, 12:100, 15:100, 18:100 or 20:100, etc. This is conducive to promoting the reaction and improving the sintering efficiency.
[0085] In some embodiments, the D of the second mixture 50 The thickness is 0.2 μm to 0.6 μm, for example, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm or 0.6 μm, etc. This is beneficial to improving the rate performance of the lithium ion battery.
[0086] In principle, the present application does not limit the solvent and solid content used in the first grinding and the second grinding, as long as they can be fully dispersed and do not chemically react with the phosphorus source, manganese source, iron source, lithium source, and M source. For production cost considerations, the solvent in the present application can be deionized water, and the solid content can be ≥30%.
[0087] In principle, this application does not limit the parameters of grinding and spray drying, as long as the D 50 The slurry with the required particle size can be dried into spherical powder. Those skilled in the art can set the parameters according to the equipment conditions.
[0088] S3: performing a second spray drying on the second mixed material to obtain a second spray-dried material.
[0089] Specifically, the particle size D of the second mixed material may be 50When the particles are ground to 0.2 μm to 0.6 μm, the second spray drying is performed.
[0090] S4: performing secondary sintering on the second spray-dried material to obtain the lithium manganese iron phosphate.
[0091] In some embodiments, the second spray-dried material is subjected to secondary sintering, comprising: heating to 600°C to 800°C (such as 600°C, 650°C, 700°C, 750°C or 800°C) at a heating rate of 1°C / min to 3°C / min (such as 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min or 3°C / min) under an inert atmosphere, and keeping the temperature for 5h to 20h (such as 5h, 8h, 10h, 12h, 15h, 18h or 20h). This can promote the reaction and improve the reaction efficiency.
[0092] The above method of the present application has at least the following technical effects:
[0093] (1) The process for preparing lithium manganese iron phosphate positive electrode materials provided in the present application has a higher degree of crystallization of the prepared positive electrode materials. There is no need to mix large and small particles, and secondary particles of both large and small sizes can be obtained, thereby achieving a higher compaction density while also taking into account better electrochemical performance.
[0094] (2) The preparation process of the lithium manganese iron phosphate positive electrode material provided in this application is simple, the cost is relatively low, and it is suitable for industrialization.
[0095] The third aspect of the present application provides a lithium-ion battery, comprising the positive electrode material described in the first aspect of the present application or the positive electrode material prepared by the method described in the second aspect of the present application. Thus, the lithium-ion battery has a higher energy density and excellent cycle stability.
[0096] It can be understood that there is no particular limitation on the specific type of the lithium-ion battery, which can be a primary battery or a secondary battery; the shape of the lithium-ion battery can be a cylindrical battery, a square battery or a battery of any other shape, etc., and according to the outer packaging classification, it can be a hard shell battery, a soft pack battery, etc.
[0097] Typically, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly by winding or lamination process, and the electrode assembly and the electrolyte can be contained in an outer package. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting active ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, which mainly plays the role of preventing the positive and negative electrodes from short-circuiting, and at the same time allows active ions to pass through.
[0098] In some embodiments, the positive electrode sheet may include a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, the positive electrode active material layer includes the lithium manganese iron phosphate positive electrode material, the conductive agent and the binder described in the present application, and the positive electrode current collector may include a metal foil, for example, the metal foil may be aluminum foil. The conductive agent may include acetylene black, single-walled carbon nanotubes and conventional materials in the art. The binder may be polyvinylidene fluoride (PVDF) and conventional materials in the art.
[0099] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, the negative electrode active material layer may include a negative electrode active material, a thickener, a conductive agent and a binder, wherein the negative electrode current collector may be a metal foil, for example, the metal foil may be a copper foil. The negative electrode active material may include artificial graphite, natural graphite, a silicon-containing carbon-based composite material, a lithium-containing metal composite material, a lithium metal material and a common negative electrode active material in the art. The thickener may be a thickener sodium carboxymethyl cellulose (CMC-Na) and a conventional material in the art. The conductive agent may be acetylene black and a conventional material in the art. The binder may be styrene-butadiene rubber and a conventional material in the art.
[0100] In some embodiments, the separator may be a separator known in the art that can be used in batteries and is stable to the electrolyte used, such as a polyethylene separator, a polypropylene separator, a polyethylene / polypropylene composite separator, and the like.
[0101] The fourth aspect of the present application provides an electric device, comprising the lithium-ion battery described in the third aspect of the present application. Thus, the electric device has a longer service life.
[0102] In some embodiments, the lithium-ion battery can be used as a power source for the power-consuming device, or as an energy storage unit for the power-consuming device. The power-consuming device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.
[0103] The embodiments of the present application are described in detail below.
[0104] Example 1
[0105] Step S1: lithium carbonate, iron phosphate, manganese tetraoxide, magnesium oxide, and lithium dihydrogen phosphate are weighed and prepared according to the molar ratio of Li, Mn, Fe, Mg, and P of 1.050:0.581:0.387:0.032:1.035, and the carbon source glucose accounts for 5.0% of the theoretical output of lithium manganese iron phosphate. The solvent deionized water is added, and the solid content is controlled at 40wt%. The ball mill (rotation speed is 2000rpm) is used for mixing. 50 When the particle size reaches 0.25 μm, the machine is stopped to obtain the secondary grinding material;
[0106] Step S2: The material obtained in step S1 is fed into the feed port of a centrifugal atomizing dryer (the inlet temperature is set at 225°C, and the outlet temperature is controlled at 100±5°C) to obtain a primary spray-dried material. The dried material is heated to 600°C at a heating rate of 2°C / min under N2 atmosphere, and kept at this temperature for 6 hours. After cooling with the furnace, a primary sintered material is obtained (SEM shows Figure 1 shown);
[0107] Step S3: The primary sintered material obtained in step S2 is weighed and mixed with glucose and polyethylene glycol in a mass ratio of 100:5:5, and dispersed in deionized water with a solid content of 50 wt %. The mixture is ground in a ball mill (rotation speed of 2000 rpm). 50 When the particle size reaches 0.35 μm, the machine is stopped to obtain the secondary grinding material;
[0108] Step S4: The material obtained in step S3 is fed into the feed port of a centrifugal atomizing dryer (the inlet temperature is set to 225°C, and the outlet temperature is controlled at 100±5°C) to perform spray drying to obtain a secondary spray-dried material, which is heated to 750°C at a heating rate of 1.5°C / min in a N2 atmosphere, kept warm for 15h, and then cooled with the furnace to obtain the lithium manganese iron phosphate positive electrode material A1, whose SEM shows Figure 2 As shown in the figure, a mixture of large and small primary particles can be seen in the field of view. The grain size distribution is calculated by XRD. Figure 3 as shown in .
[0109] Example 2
[0110] According to the method of Example 1, except that in step S1, the molar ratio of Li, Mn, Fe, Mg, and P is 1.050:0.581:0.387:0.032:1.030, and the rest are the same, the lithium manganese iron phosphate positive electrode material A2 is obtained, and the grain size distribution is calculated by XRD. Figure 3 as shown in .
[0111] Example 3
[0112] The method of Example 1 is followed, except that in step S1, the molar ratio of Li, Mn, Fe, Mg, and P is 1.050:0.581:0.387:0.032:1.080, and the rest are the same, to obtain the lithium manganese iron phosphate positive electrode material A3.
[0113] Example 4
[0114] The method of Example 1 is followed, except that in step S1, the molar ratio of Li, Mn, Fe, Mg, and P is 1.050:0.581:0.387:0.032:1.010, and the rest are the same, to obtain the lithium manganese iron phosphate positive electrode material A4.
[0115] Example 5
[0116] The method of Example 1 is followed, except that in step S1, the molar ratio of Li, Mn, Fe, Mg, and P is 1.050:0.775:0.194:0.031:1.035, and the rest are the same, to obtain the lithium manganese iron phosphate positive electrode material A5.
[0117] Example 6
[0118] The method of Example 1 is followed, except that in step S1, the molar ratio of Li, Mn, Fe, Mg, and P is 1.050:0.581:0.387:0.032:1.000, and the rest are the same, to obtain the lithium manganese iron phosphate positive electrode material A6.
[0119] Example 7
[0120] The method of Example 1 is followed, except that in step S2, the primary dried material is heated to 400° C. at a heating rate of 2° C. / min under a N2 atmosphere and kept warm for 6 h, and the rest is the same to obtain the lithium manganese iron phosphate positive electrode material A7.
[0121] Example 8
[0122] The method of Example 1 is followed, except that in step S2, the primary dried material is heated to 750° C. at a heating rate of 2° C. / min under a N2 atmosphere and kept warm for 6 h, and the rest is the same to obtain the lithium manganese iron phosphate positive electrode material A8.
[0123] Example 9
[0124] The method of Example 1 is followed, except that in step S4, the secondary spray-dried material is heated to 600° C. at a heating rate of 1.5° C. / min under a N2 atmosphere and kept warm for 15 h, and the rest is the same to obtain the lithium manganese iron phosphate positive electrode material A9.
[0125] Comparative Example 1
[0126] The method of Example 1 is followed, except that in step S1, the molar ratio of Li, Mn, Fe, Mg, and P is 1.050:0.581:0.387:0.032:0.930, and the rest is the same to obtain the lithium manganese iron phosphate positive electrode material D1. The SEM of the primary sintered material is shown in FIG. Figure 4 As shown, the finished product SEM Figure 5 As shown, the finished product is calculated by XRD statistical grain size distribution as shown Figure 3 as shown in .
[0127] Comparative Example 2
[0128] The method of Example 1 is followed, except that in step S2, the dried material is heated to 380°C at a heating rate of 2°C / min in a N2 atmosphere and kept warm for 6 hours, and the rest is the same to obtain the lithium manganese iron phosphate positive electrode material D2. The finished product is statistically calculated by XRD to have a grain size distribution as shown in FIG. Figure 3 as shown in .
[0129] The relevant parameters of the above embodiments and comparative examples were obtained by testing using the following methods:
[0130] (1) SEM test: obtained by scanning electron microscope S-4800 of Hitachi, Japan;
[0131] (2) Primary particle size P: The projected area of each single crystal particle in the electron microscope is counted, and then its particle size is calculated. The specific method is: the average diameter is calculated by converting the projected area of 300 random primary particles in the scanning electron microscope image into a standard circle of equal area, that is, the primary particle size P of the primary sintered material in the preparation process of lithium manganese iron phosphate positive electrode material;
[0132] (3) Unit cell volume test: tested by Rigaku rotating target diffractometer Smartlab 9KW, range 10-80°, voltage 40kV, current 200mA, step 0.02°, scanning time 2° / min. The test results were refined and calculated using the WPPF method of SmartLab Studio II software to obtain the unit cell volume;
[0133] (4) Grain size L 10 , L 50 , L 90:Tested by Rigaku rotating target diffractometer Smartlab 9KW, range 10-80°, voltage 40kV, current 200mA, step 0.02°, scanning time 2° / min. The test results were obtained by using the WPPF grain size distribution function of SmartLab Studio II software according to the Fundamental Parameter method (FP method) to perform grain size statistics. The grain size distribution diagrams of the finished positive electrode materials of Example 1, Example 10, and Comparative Example 1 are shown in Figure 3 ;
[0134] (5) Compacted density test: The compacted density test was conducted using the MCP-PD51 compacted density tester produced by Mitsubishi Chemical of Japan. 1±0.01 g of sample was weighed and the pressure was 3T.
[0135] (6) Electrochemical performance test: In the following examples and comparative examples, the electrochemical performance test of R2025 button cells was carried out using Shenzhen Xinweier Battery Testing System. The first charge and discharge capacity test conditions were: 25°C, 0.1C charge and discharge, voltage range 2.5-4.35V, and charging constant voltage cutoff current of 0.05C. The battery preparation process is as follows:
[0136] Preparation of pole pieces: The positive electrode material, conductive agent SuperP and polyvinylidene fluoride (PVDF) were mixed with an appropriate amount of N-methylpyrrolidone (NMP) in a mass ratio of 90:5:5 to form a uniform slurry. The slurry was coated on aluminum foil and dried at 120°C for 12 hours. It was then stamped into a positive electrode piece with a diameter of 12 mm and a thickness of 120 μm using a pressure of 100 MPa.
[0137] Battery assembly: In an argon-filled glove box with a water content and oxygen content of less than 5ppm, the positive electrode sheet, separator, negative electrode sheet and electrolyte were assembled into R2025 button cells and left to stand for 6 hours. The negative electrode sheet used a metal lithium sheet with a diameter of 15.6mm and a thickness of 0.45mm; the separator used a 25μm polypropylene microporous membrane (Celgard 2325); and the electrolyte used an equal mixture of 1mol / L LiPF6, ethylene carbonate (EC) and diethyl carbonate (DEC).
[0138]
[0139] It can be seen from the above test results that, compared with the comparative example, the lithium iron manganese phosphate positive electrode material prepared by the method described in the present application has a higher degree of crystallization, a larger primary particle size and a suitable grain size distribution, and a higher compaction density and electrochemical capacity. The molar ratio of P / (Mn+Fe) and the conditions of the sintering treatment are crucial for the preparation of a specific primary sintered material and a specific lithium iron manganese phosphate positive electrode material product. Specifically, compared with Example 1, the P content of Example 3 increases, which is not within the preferred range of the present application, resulting in an increase in compaction density and a decrease in capacity; the P content of Example 4 decreases, which is not within the preferred range of the present application, resulting in a decrease in both compaction density and capacity; the P content of Example 6 is too small, which is not within the preferred range of the present application, resulting in a greater decrease in compaction density and capacity; the primary sintering temperature of step S2 in Example 7 is relatively low, and the grain size is small, resulting in a decrease in compaction density and capacity; the primary sintering temperature of step S2 in Example 8 is relatively high, and the grain size is too large, resulting in a decrease in capacity; the secondary sintering temperature of step S4 in Example 9 is relatively low, and the unit cell volume and grain size are both reduced, resulting in a decrease in compaction density and capacity; while the P content in comparative example 1 is too low, which is not within the scope of the present application, resulting in a primary particle size that is too small, and the unit cell volume and grain size are also too small, resulting in poor compaction density and capacity; the primary sintering temperature of step S2 in comparative example 2 is too low, and the unit cell volume and grain size are too small, resulting in poor compaction density and capacity. In general, the preparation process provided in this application can effectively improve the compaction density and electrochemical capacity of lithium manganese iron phosphate positive electrode materials.
[0140] In the description of the present application, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present application, "plurality" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0141] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0142] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A positive electrode material, characterized in that: Including lithium manganese iron phosphate, the unit cell volume of the lithium manganese iron phosphate is 2. The positive electrode material according to claim 1, characterized in that The unit cell volume of the lithium manganese iron phosphate is Preferably 3. The positive electrode material according to claim 1 or 2, characterized in that The lithium manganese iron phosphate has a composition shown in Formula I: Li a Mn x Fe y M 1-x-y (PO4) b Formula I Among them, 0.90≤a≤1.20, 0.30≤x≤0.95, 0.05≤y≤0.70, 0.95≤b≤1.10; M is at least one selected from Ti, Mg, Zn, Cu, Sr, Al, Zr, Y, Co, W, Ca, Nb, Sn, Sb, Mo, V, B, and Si; 1.03≤b / (x+y)≤1.
15.
4. The positive electrode material according to claim 3, characterized in that Satisfy at least one of the following conditions: 0.95≤a≤1.15, preferably 1.00≤a≤1.10, more preferably 1.02≤a≤1.08; 1.00≤b≤1.09, preferably 1.01≤b≤1.07; 0.90≤x+y≤1.00, preferably 0.95≤x+y<1.00; 1.05≤b / (x+y)≤1.
10.
5. The positive electrode material according to claim 1, characterized in that The lithium manganese iron phosphate meets the following requirements: 80nm≤L 10 ≤200nm, preferably 100nm≤L 10 ≤180nm; 150nm≤L 50 ≤300nm, preferably 160nm≤L 50 ≤260nm; 200nm≤L 90 ≤500nm, preferably 220nm≤L 90 ≤480nm; Among them, L 10 , L 50 , L 90 It is the grain size corresponding to when the volume cumulative percentage of the grain size Ln of the lithium manganese iron phosphate reaches 10%, 50% and 90% respectively.
6. The positive electrode material according to claim 1, characterized in that The compacted density of the lithium manganese iron phosphate is 2.3 g / cm 3 ~2.6g / cm 3 .
7. A method for preparing the positive electrode material according to any one of claims 1 to 6, characterized in that: include: Sintering a first mixed material containing a lithium source, an M source, a phosphorus source, a manganese source, and an iron source to obtain a primary sintered material, wherein the primary sintered material includes secondary particles, wherein the secondary particles are formed by agglomerating a plurality of primary particles, and a primary particle size P of the primary particles satisfies 100 nm ≤ P ≤ 500 nm; Mixing the primary sintered material with a carbon source in a solvent and performing a second grinding to obtain a second mixed material; The second mixed material is subjected to a second spray drying to obtain a second spray-dried material; The second spray-dried material is subjected to secondary sintering to obtain the lithium manganese iron phosphate.
8. The method according to claim 7, characterized in that Performing a first spray drying on the first mixed material to obtain a first spray-dried material; The first spray-dried material is heated to 400° C. to 700° C. at a heating rate of 1° C. / min to 5° C. / min under an inert atmosphere, and kept at this temperature for 3 h to 15 h, and then sintered once to obtain a primary sintered material.
9. The method according to claim 7, characterized in that: The molar ratio n(P) / n(Mn+Fe) of phosphorus in the phosphorus source to manganese in the manganese source and iron in the iron source is 1.03:1 to 1.15:
1.
10. The method according to claim 7, characterized in that The first mixture D 50 0.1 μm to 0.5 μm; and / or The second mixture D 50 It is 0.2μm~0.6μm.
11. The method according to claim 7, characterized in that The mass ratio of the carbon source to the primary sintering material is 2:100 to 20:
100.
12. The method according to claim 7, characterized in that Satisfy at least one of the following conditions: The manganese source includes at least one of manganese sulfate, manganese carbonate, manganese nitrate and manganese tetraoxide; The iron source includes at least one of ferric phosphate, ferric nitrate, ferric sulfate, ferrous oxalate, ferrous carbonate, and ferric oxide; The phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate, lithium dihydrogen phosphate, and lithium phosphate; The lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium phosphate and lithium nitrate; The M source includes at least one of an oxide, a hydroxide, and a carbonate containing the M element; The carbon source includes at least one of glucose, sucrose and organic polymers.
13. The method according to claim 7, characterized in that The second spray-dried material is subjected to secondary sintering, comprising: heating the material to 600° C. to 800° C. at a heating rate of 1° C. / min to 3° C. / min under an inert atmosphere, and keeping the temperature for 5 hours to 20 hours.
14. A lithium ion battery, characterized in that: The invention comprises the positive electrode material according to any one of claims 1 to 6 or the positive electrode material prepared by the method according to any one of claims 7 to 13.
15. An electrical device, characterized in that: Includes the lithium ion battery as claimed in claim 14.
Citation Information
Cited By
Positive electrode material and preparation method thereof, lithium ion battery and electric device
CN120237203A